Notas de um Plano Nacional de Capacitação Financeira - Fernando Batista Pereira (2015)
The thesis aims to draw up a financial capability national plan for households to meet economic and social demands, stemming from the financialization process in recent decades. Firstly, a critical analysis of the called "conventional" approach is performed, according to which the gist of a financial capability plan would be through financial education initiatives. The conventional argument is that increasing financial knowledge of families will enable them to make better decisions to promote financial welfare gains for the families and the economy as a whole. Despite a broad political and academic support in favor of the conventional proposal, empirical results of financial education initiatives are modest and controversial, according to literature. At the same time, a critical analysis of Annamaria Lusardis discourse one of the leading exponents of conventional approach has demonstrated its fragility and theoretical inconsistency, contrary to scientific rigor advocated by the author. After that, critical authors to conventional proposal, categorized as institutionalist by the thesis, are analyzed. First of all, institutionalist approach has incorporated behavioral analysis theory, questioning the conventional hypothesis that families predominantly make decisions based on knowledge and information, in a rational logic. Moreover, institutionalists assume that financial capability of families cannot be restricted to individual treatment but should incorporate the entire financial system, due to large imbalance and potential conflict between consumers and financial institutions. The first contribution of this thesis is to complement institutionalist approach with post-Keynesian theoretical baggage, specifically fundamental uncertainty and minskyan business cycle theory concepts. These two concepts allow the complete refusal of the conventional argument that financially educated individuals take on "optimal" decision. Another thesis contribution is to propose main principles of a national plan of financial capability, through three instruments: financial education, financial advice and regulation and protection system of financial consumer. Financial education must deal with basic level of personal finance, incorporating notions of uncertainty and economic instability, in addition to behavioral biases elements. Financial advice will be provided as financial advisory services by independent professionals offering from general financial information to sophisticated services, such as guidance to families to tackle financial crisis. In addition to these, the thesis proposes regulatory guidelines and protection system to financial consumers, in order to curb undesirable practices used by financial institutions, in addition to handling cases of family overindebtedness. Finally, the thesis proposes a financial capability index, able to diagnose, monitor and evaluate the performance of the national plan.